Biomechanical Analysis of Dollyo Chagi Kicks in Taekwondo Athletes in Indonesia - Evi Susianti (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This literature review examines Indonesian national research published between 2021 and 2024 regarding the biomechanical aspects of the dollyo chagi kick in taekwondo. The review focuses on kinematic and kinetic parameters such as joint angles, peak angular velocity, hip–knee–ankle sequencing, and foot linear velocity, as well as relationships between leg explosive power and kick performance. The analysis indicates consistent findings that optimized movement sequencing and increased lower-limb explosive power improve kick speed and impact. Methodological limitations include small sample sizes and limited use of advanced tools such as 3D motion capture and force plates. Recommendations for future research include longitudinal studies and standardized biomechanical assessment protocols.